Cultural and socioeconomic influences on divorce during modernization : Southeast Asia, 1940s to 1960s - Hirschman, CH.; Teerawichitchainan, B.
tbls.
pp. 215-253
Keywords: Cultura; Sociedad; Economía; Divorcio; Familia; Asia Sudoriental; Siglo XX